遷移世代的敘事探究：維妮的故事 Narrative Inquiry of Moving Generation: Winnie's Story - 王慧玉Sophie Hui-Yu Wang (Higher Education Foundation, 2010)
漂流，因而生命有無限可能；遷移，因而生命有如河流般長遠。本文敘事探究描述的是一位臺商子女維妮在中國大陸的教育與文化經驗。從13歲小學畢業後，進入中國大陸的教育體制，維妮在當地求學10年，從中學到大學，求學、就職經歷共有13年之久。維妮，具有不同於臺灣成長的教育經歷，臺商子女面臨哪些成長經歷、認同和自由的選擇，遷移世代具有如何與眾不同的文化特質？我們教育可以關心的是什麼？可以做些什麼？遷移如何造就新的一代？他們又如何思索自己與文化、地方的觀念？女性主義常常批判主流意識的許多看法，多元詮釋和看法與主流不同，並產生新的故事。敘事探究中，研究者與維妮一起探索建構和協商合作她的故事。在後殖民文學中，Naipaul也曾分析自己這樣的文化碰撞，認為認同鬆散的人，反而使自己處於「建構／拆解」、「接納／拒絕」、「同化／異化」的曖昧狀態，卻也使他創作出靈魂的文本，超越國界的人類關懷。瞭解遷移世代具有自我敘說的文本，說出他們的故事，也道出教育中少數族群的位置所在。 The study focuses on "Moving Generation". The girl lived in the Mainland China about 13 years. The Children of Taiwanese Businessmen name is "Winnie" This research's methodology included the literature review, narrative inquiry. Through Winnie's story, we can understand her life and identity. What do they learn there and whether children can adapt to their life? Winnie has deep experience and local culture in Mainland China. Understand "Moving Generation" have their story and social context. And we can face up to a great diversity of the generation.